The Journey of a Massage Therapist’s Experience After Receiving a Formal Complaint - Kennedy, LMT, BCTMB, DrPH, Ann Blair (International Journal of Therapeutic Massage & Bodywork, 2021)
Discussions of professionalism and conflict within practice are an important area of enquiry as massage therapy practice continues to be recognized within the health care realm. The scientific literature has paid little attention to these massage therapy professional and ethical dilemmas. Herein, we explore one such area of conflict between a client and therapist in regard to communication and complaints. An interview was conducted to gain further insight to the situation and is structured based upon the following interview guide: description of the instance, how the therapist handled this situation, reflection on how the therapist’s actions contributed to the situation, brief discussion of how other professions handled these types of situations, and reflection on what could have been done differently.